A case report of seizure worsening after perampanel add-on to oxcarbazepine: possible role of metabolic interaction and pharmacogenetics - Fang, Xin; Zhu, Menglu; Wang, Lijiang (Frontiers in Psychiatry, 2025)
ObjectiveTo investigate the factors contributing to increased seizure frequency in patients treated with a combination of oxcarbazepine (OXC) and perampanel.MethodsThe influence of the combined use of perampanel and oxcarbazepine on pharmacokinetics was analyzed, and the results were further confirmed by scoring the Naranjo Adverse Reaction Scale. The influence of race on antiseizure medications (ASMs) was also analyzed.ResultsThe concomitant use of perampanel and oxcarbazepine increased the plasma concentration of oxcarbazepine. Scoring with the Naranjo adverse reaction scale indicated that the deterioration of seizures in patients following the addition of perampanel may be associated with the interaction of the two drugs.ConclusionThe exacerbation of epilepsy in patients may be attributed to the increased blood concentration of oxcarbazepine resulting from its combination with perampanel, which potentially triggers a worsening of seizures. Variations in gene mutations related to Asian factors, as well as differences in drug metabolism enzymes and transporters, may also contribute to alterations in the concentration of ASMs.